"If I Could Turn Back Time": Occupational Dynamics, Technology Trajectories, and the Reemergence of the Analog Music Synthesizer*. (June 2023) - Nelson, Andrew; Anthony, Callen; Tripsas, Mary
There are numerous examples of the reemergence of old technology, such as vinyl records and film cameras. Yet, the literature on technology trajectories has focused almost exclusively on linear models of technology progression, and we have little understanding of the processes that may instead drive reemergence. In fact, no prior research has examined how users' occupational considerations may shape technology trajectories, despite a large literature on how occupations condition interactions with technological tools. This article sheds light on these processes through an inductive study of the music synthesizer industry's shifts from analog to digital and back to analog technology. Leveraging more than 40 years of data, we trace the relationship between technological developments and synthesizer players' occupational meaning. While synthesists initially embraced the ease of use and novelty of digital's black-boxed preset sounds, widespread adoption of digital sounds ultimately undermined musicians' occupational goal of distinctive creative expression. In response, synthesists articulated preferences for technology that afforded control, enabling them to use their expertise to create sounds, and that provided an embodied connection with the tool. Synthesists associated these affordances with analog rather than digital instruments, leading to renewed demand for analog and the reemergence of a formerly displaced technology. Our work integrates occupational considerations into the literature on technology trajectories, uncovers new mechanisms that can underlie technology reemergence, and extends the literature on occupations and technology.